2007
DOI: 10.1038/sj.ijo.0803543
|View full text |Cite
|
Sign up to set email alerts
|

Levels of C3 in patients with severe, morbid and extreme obesity: its relationship to insulin resistance and different cardiovascular risk factors

Abstract: Objective: Increased C3 has been related to body mass index (BMI) and insulin resistance, although there are not sufficient studies in subjects with morbid obesity. The purpose of this study was to evaluate the levels of C3 as a function of the BMI in subjects of both sexes, with severe, morbid and extreme obesity, and their possible relationship to insulin resistance or associated diseases such as diabetes, hypertension and dyslipidemia. Subjects: The study included a total of 316 patients (110 men and 206 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 26 publications
(24 reference statements)
10
38
0
Order By: Relevance
“…This may to some extent be interpreted as simple confounding since abdominal obesity is a known determinant of both IR and plasma C3 levels (3,(41)(42)(43). However, the relationship of waist circumference with C3 is not straightforward, because abdominal obesity may also be considered an ascending proxy in the causal pathway between C3 and IR (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may to some extent be interpreted as simple confounding since abdominal obesity is a known determinant of both IR and plasma C3 levels (3,(41)(42)(43). However, the relationship of waist circumference with C3 is not straightforward, because abdominal obesity may also be considered an ascending proxy in the causal pathway between C3 and IR (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Complement factor 3 (C3) is an emerging risk marker for cardiovascular and metabolic diseases (1,2), and systemic C3 concentrations are closely linked to several measures of body fat and components of the metabolic syndrome (3,4). Complement C3 is produced mainly by the liver (5), but other production sites, such as adipose tissue, may also contribute to systemic C3 levels (6).…”
mentioning
confidence: 99%
“…Insulin resistance has consistently been associated with a high serum level of C3 in a potentially causal manner [13][14][15][16] . However, the physiological mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We used the gold standard hyperinsulinemic euglycemic clamp technique enabling us to distinguish between hepatic and peripheral insulin resistance. Previous studies have reported associations between high circulating levels of C3 and insulin resistance using the more indirect homeostasis model assessment of insulin resistance (HOMA-IR) [13][14][15][16] . HOMA-IR predominantly reflects hepatic insulin resistance indirectly supporting our results.…”
mentioning
confidence: 99%
See 1 more Smart Citation